Changes in spectral quality of underwater light alter phytoplankton community composition. Issue 9 (2nd July 2021) - Hintz, Nils Hendrik; Zeising, Moritz; Striebel, Maren
Abstract: Light is a fundamental resource for phytoplankton. To utilize the available light, most phytoplankton species possess pigments in taxon‐specific combinations and quantities, which in turn result in a specific use of certain wavelengths. This optimizes the light use efficiency, allows for a complementary use of light, and may be an additional driver for community structure. While the effects of light intensity on phytoplankton biomass production and community composition have been intensively studied, here we focused on the effects of specific light spectrum quality (thus light color) on a natural phytoplankton community. In a controlled mesocosm experiment we reduced the supplied wavelength range to its blue, green, or red part of the light spectrum and compared the responses of each treatment to a full spectrum control over 28 d. Highest community growth rates were observed under blue, lowest under red light. Light absorption by the communities showed adaptation toward the supplied wavelength range. Community composition was significantly affected by light quality treatments, driven by Bacillariophyta and Chlorophyta, whereas pigment composition was not. Furthermore, lower species richness but higher evenness occurred when communities were exposed to red light compared to the full spectrum. We expected the response of phytoplankton communities to changes in the light spectrum to be driven by a combination of species sorting and pigment acclimation; however, the effect of species sorting turned out to be stronger. Our study showed that, even if species might acclimate, changes in the available light spectrum affect primary production and phytoplankton community composition.